2013
DOI: 10.1093/rheumatology/ket226
|View full text |Cite
|
Sign up to set email alerts
|

Does geographic location affect incidence of ANCA-associated renal vasculitis in northern Saskatchewan, Canada?

Abstract: The incidence of renal biopsy-proven AAV was higher in patients living in northern Saskatchewan smaller communities and rural settings. A significantly longer time to diagnosis existed for patients outside the urban centre and was associated with poorer BVAS, VDI and FFS scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…This predominance of MPA over GPA in renal involvement was also observed in Spain, Japan and Canada (Northern Saskatchewan), with latitudes 40 o N, 36 o N and 55 o N, respectively. 29 35 36 In comparison with European regions with similar latitudes to Scotland, our results are at variance. In the Netherlands (latitude 52 o N), GPA is twice as common as MPA in patients with AAV and renal involvement.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This predominance of MPA over GPA in renal involvement was also observed in Spain, Japan and Canada (Northern Saskatchewan), with latitudes 40 o N, 36 o N and 55 o N, respectively. 29 35 36 In comparison with European regions with similar latitudes to Scotland, our results are at variance. In the Netherlands (latitude 52 o N), GPA is twice as common as MPA in patients with AAV and renal involvement.…”
Section: Discussionmentioning
confidence: 69%
“…Therefore, results may not be representative for AAV. Looking at renal AAV, Anderson et al 29 observed higher incidences of renal AAV in rural Northern Saskatchewan, Canada (16.5 cases pmp/year in rural areas compared with 6.1 pmp/year in urban areas), but this was a small study of only 33 cases of renal AAV. Exposure to farming (OR 2.3 (95% CI 1.2 to 4.6)) has previously been considered as a contributory factor, and our data support exploring this further.…”
Section: Discussionmentioning
confidence: 84%
“…There are also studies investigating the influence of living in rural versus urban areas. The incidence of AAV was significantly higher in rural areas compared to urban areas in studies from Australia and Canada [71,96], while such a pattern was not seen for MPA and GPA in a Spanish study [76].…”
Section: Geographical Differencesmentioning
confidence: 79%
“…Studies in Scotland, Germany, and Canada showed that the incidence of AAV in rural areas is higher than that in cities. This may be related to environmental pollutants and pesticide exposure in remote areas (68,72,78,79). Additionally, a large Swedish case-control study (73) found no association between occupation and GPA (Table 1).…”
Section: Air Pollutionmentioning
confidence: 99%